Development of ARcell Apps for The Topic of the Structure of Cells and Organelles - Hashim, Rohani Binti; Ahmad, Che Nidzam Che’; Noor, Nor Nafizah Binti Mohd; Nizam, Nur Zakirah binti Mohd; Salleh, Wan Nasriha Wan Mohamed; Setyaningsih, Endang (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research aimed to develop and evaluate the level of usability of Augmented Reality apps named ARcell for the topic of The Structure of Cells and Organelles. The research design used was development research. The development of this ARcell apps was based on the ADDIE model, with the integration of Constructivism learning theory and Mayer Cognitive theory of multimedia learning. The validity of the ARcell apps was determined by experts, while the reliability was based on the pilot study. The level of usability of ARcell apps was determined through 101 Form 6 student’s perceptions randomly selected from three schools in Malacca. The data were analyzed descriptively using the SPSS software. The findings showed that the ARcell mobile apps had good validity from the content aspect (S- CVI = 1.00), technical aspect (S- CVI = 0.97) and also had good reliability with Cronbach’s Alpha value of 0.94 from the student’s perspective. ARcell mobile apps also had good usability in terms of design, functionality, ease of use, learnability, satisfaction, future use, and system reliability, with a high mean value of 3.94. Essentially, the ARcell apps had good validity, reliability and usability and are very suitable for the use in the learning of Form 6 biology in the topic of Cell Structure and Organelles. The implications of this study indicated that the ARcell mobile apps could be used as an additional teaching aid and can be a catalyst for a new global learning approach in Malaysia. It is very relevant and practical particularly in applying student self-learning during the country as well as the rest of the world facing the Covid-19 pandemic situation.